KONDISI UMUM HUTAN MANGROVE DI PROVINSI RIAU BERDASARKAN RISET DI BEBERAPA TITIK - Yasin Setiawan; Yusri Yusri; Sukendi Sukendi (Pelantar Press, 2025)
Mangrove forests in Riau Province play a vital role in carbon sequestration, coastal protection, and marine biodiversity conservation. This research examines the general condition of mangrove forests in Riau Province through literature review and content analysis of scientific articles published between 2017-2021. With a total area of 138,434 hectares distributed across seven regencies and cities, Riau's mangrove forests demonstrate significant carbon storage capacity, estimated at approximately 148 million tons of CO2 absorption. The research focuses on multiple observation points including Indragiri Hilir, Siak, Dumai, and Kepulauan Meranti to assess mangrove density, vegetation diversity, and ecological conditions. The findings reveal a concerning trend of declining mangrove coverage over the years, with vegetation area decreasing from 9,759 ha in 1997 to 7,875 ha in 2019 in Pulau Rangsang alone. Industrial activities, particularly oil industries operating in Riau Province, have been identified as significant factors affecting mangrove quality through heavy metal contamination (Pb), pH changes, and dissolved oxygen levels in coastal waters. Despite these challenges, mangrove forests in Riau continue to support diverse marine biota, with studies documenting 14 true mangrove species and 8 associated species in Sungai Pakning, and various zooplankton communities in Bandar Bakau. The research underscores the urgent need for comprehensive conservation policies and rehabilitation efforts to preserve Riau's mangrove ecosystems and their critical environmental functions.